STRENGTHENING THE CYBER DEFENSE CENTER OF THE MINISTRY OF DEFENCE OF THE REPUBLIC OF INDONESIA (PUSDATIN KEMHAN) TO SUPPORT THE INDONESIAN DEFENSE DIPLOMACY IN CYBER DEFENSE SECURITY COOPERATION IN ASEAN - Rifani Agnes Eka Wahyuni; Surryanto Djoko Waluyo; Haposan Simatupang (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2021)
The development of information technology in the international world impacts cyberspace, covering all aspects of national life. So, the government must understand the condition of cyber security in Indonesia and build a national defense system to overcome various threats that come through cyberspace. ASEAN has become one of the platforms for Indonesia to fight for its national interests to support national security in the cyber field. The purpose of this research is to analyze the efforts to strengthen the national defense system based on five aspects of cybersecurity capacity building to realize Indonesia's defense development in cyber defense security through the role of Cyber Defense Center as an actor in Indonesia's defense diplomacy in enhancing cyber defense security cooperation in ASEAN. These strategies and efforts were analyzed through a qualitative approach, and primary data were collected through interviews with informants from various government agencies. In addition, literature, journals, and related documents are also used as supporting data. These efforts resulted in an agreement in the form of making a cyber-portal between countries and equality of view to continue to conduct cybersecurity training in the form of seminars and workshops to build the capacity of the national defense system.